Strata calculator: mobile application to facilitate share unit and charges for stratified and landed strata / Arisya Azmira Noor Azmi, Nurin Azimah Mohd Taufik and Saharuddin Lin - Noor Azmi, Arisya Azmira; Mohd Taufik, Nurin Azimah; Lin, Saharuddin (College of Built Environment, 2023)
Share unit value is important in calculating maintenance fee in Strata Title. This study aims to develop a strata calculator mobile application for calculating share unit and charges that include maintenance fee and sinking fund.